Improving Distributed Denial of Service (DDOS) Detection using Entropy Method in Software Defined Network (SDN) - Abdurohman, Maman; Prasetiawan, Dani; Yulianto, Fazmah Arif (ComTech: Computer, Mathematics and Engineering Applications, 2017)
This research proposed a new method to enhance Distributed Denial of Service (DDoS) detection attack on Software Defined Network (SDN) environment. This research utilized the OpenFlow controller of SDN for DDoS attack detection using modified method and regarding entropy value. The new method would check whether the traffic was a normal traffic or DDoS attack by measuring the randomness of the packets. This method consisted of two steps, detecting attack and checking the entropy. The result shows that the new method can reduce false positive when there is a temporary and sudden increase in normal traffic. The new method succeeds in not detecting this as a DDoS attack. Compared to previous methods, this proposed method can enhance DDoS attack detection on SDN environment.